Personality Traits and Cyberbullying Perpetration Among Chinese University Students: The Moderating Role of Internet Self-Efficacy and Gender - Xu, Wei; Zheng, Shujie (Frontiers in Psychology, 2022)
Cyberbullying is a serious global problem that affects many teenagers and university students. Recent studies have explored the relationship between personality traits and cyberbullying, but the mechanism needs further research. This paper examines the impact of personality traits on cyberbullying perpetration of Chinese university students and the moderating role of Internet self-efficacy (ISE) and gender. By random cluster sampling, 549 university students (45.7% boys) participated in filling out the self-report questionnaires. The results revealed: (1) conscientiousness, agreeableness, and openness were significantly negatively correlated with cyberbullying perpetration. (2) The stratified regression showed that ISE moderated the relation between agreeableness and cyberbullying. Gender moderated the relationship between agreeableness and cyberbullying, and openness and cyberbullying.